Aktivitas Komunikasi Dalam Pernikahan Adat Batak Toba Tahap Ulaon Marunjuk - Jessica Desirre Natalia; Agus Aprianti (UMSU, 2020)
Ulaon Marunjuk is a traditional wedding ceremony held at a guesthouse or multipurpose building. At this stage the official hand over of the dowry will be carried out.This study aims to explain the communication activities at the Toba Batak Customary wedding ceremony at the Ulaon Marunjuk stages. This study uses the ethnographic communication study method in qualitative research, with a constructivist paradigm. Researchers obtain data from interviews with resource persons, literature studies and are supported from observations. Then the results of the data are analyzed, the presentation of data in a brief description, and making conclusions. Researchers obtained results in the form of communication activities that took place at the Batak Toba traditional marriage, namely the communication situation in the marriage was solemn and sacred, obedience to customary law, warmth, excitement, crowd, excitement, commotion, lack of conducive and thick atmosphere of traditional Batak Toba tradition. The communication events illustrate in sequence about the Toba Batak traditional marriage process from the beginning to the end. Then, communication actions that describe actions or interactions that occur through verbal and non verbal communication. The results of the research in the form of Communication Activities consisting of three elements, namely the communication situation, communication events, and communication actions are key in describing the communication process found in the Batak Toba Indigenous marriage Ulaon Marunjuk Stage.